Recent Trends in Computer Networks and Distributed Systems Security Second International Conference, SNDS 2014, Trivandrum, India, March 13-14, 2014. Proceedings - Martinez Perez, Gregorio; Thampi, Sabu M.; Ko, Ryan; Shu, Lei (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the Second International Conference on Security in Computer Networks and Distributed Systems, SNDS 2014, held in Trivandrum, India, in March 2014. The 32 revised full papers presented together with 9 short papers and 8 workshop papers were carefully reviewed and selected from 129 submissions. The papers are organized in topical sections on security and privacy in networked systems; multimedia security; cryptosystems, algorithms, primitives; system and network security; short papers. The workshop papers were presented at the following workshops: Second International Workshop on Security in Self-Organising Networks (Self Net 2014); Workshop on Multidisciplinary Perspectives in Cryptology and Information Security (CIS 2014); Second International Workshop on Trust and Privacy in Cyberspace (Cyber Trust 2014).